Inclusive Disability Sports Coaching Strategy: A Case Study - Husain, Andi Baso; Ishar, A. Anwar; Bintang, Rahmat S. (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. Disabled sports in Sinjai Regency still face various challenges, despite the great potential possessed by athletes. This study aims to develop an inclusive disability sport coaching strategy in Sinjai District to increase the participation and achievement of athletes with disabilities. Material and method. Using a qualitative approach with a case study method, this research involved in-depth interviews with various stakeholders, such as the Kadispora, the Head of Koni, the National Paralympic Committee (NPC), and disabled sports activists. Result. The results showed that the main obstacles faced include the lack of licensed coaches, the lack of disability-friendly facilities and infrastructure, and the non-optimal management of NPC Sinjai. Therefore, the proposed strategies include reactivation of NPC Sinjai, recruitment of licensed coaches, improvement of facilities and infrastructure, and close collaboration between the local government and related organisations. Hopefully, the implementation of this strategy will be able to support the achievements of Sinjai disabled athletes to the national and international levels. Conclusion. With the synergy between the NPC, local government, coaches, and the community, Sinjai has a great opportunity to become a national example in creating an inclusive and supportive sports ecosystem. Consistent implementation of this strategy is expected to not only produce outstanding athletes, but also establish Sinjai Regency as a pioneer in fighting for equality and success in the field of disability sports in Indonesia.